Fungal Decolourization of Direct Azo Dyes and Biodegradation of Textile Dye Effluent - D. Stella, P. Saranraj*, V. Sumathi, D. Reetha and (Journal of Ecobiotechnology, 2010)
Abstract <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"><span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Decolourization of Direct azo dyes by fungi isolated from textile dye effluent was investigated. Seven different fungal species were isolated and identified. The fungal isolates were identified as Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus, Fusarium oxysporum, Penicillium chrysogenum, Mucor sp. and Trichoderma viride. The fungal inoculums were inoculated into flasks containing Direct azo dyes (500 mg/l) with trace amounts of yeast extract, glucose and sucrose and then sterilized and incubated for 12 days. Aspergillus niger completely decolourized the Congo Red within 6 days. The best decolourizer of Viscose Orange-A was Aspergillus fumigatus (88.70%). Mucor sp. (69.73%) was identified as the best decolourizer of Direct Green â€“ PLS. The dye Direct Violet-BL was completely decolourized by Aspergillus niger within 9 days and Trichoderma viride within 12 days. The dye Direct Sky Blue-FF was completely decolourized by Aspergillus flavus within 9 days and Mucor sp. within 12 days. Penicillium chrysogenum have the capacity to completely decolourized the dye Direct Black-E within 12 days. Fungal biodegradation was assessed by physicochemical analysis.